Optimization of a Dual-Stage Filtration Unit Using Cation Resin, Zeolite, and Activated Carbon for Limewater Treatment in Mulyosari Hamlet, Malang Regency - Fauzi, Rachmad Pratama; Sulianto, Akhmad Adi; Umar, Yasa Palaguna (Jurnal Sumberdaya Alam dan Lingkungan, 2025)
ABSTRACT Access to potable water remains a critical challenge in rural limestone regions such as Mulyosari Hamlet, Malang Regency, where groundwater is often contaminated by high levels of calcium carbonate, total dissolved solids, and alkalinity. This study aimed to evaluate the effectiveness of a simple water filtration system utilizing locally available media to reduce these contaminants and achieve compliance with national drinking water standards. The filtration unit consisted of two cylinders filled with cation exchange resin, silica sand, activated carbon, and natural zeolite, and was tested over a four-month dry season period. Groundwater samples were collected before and after treatment for chemical and hydraulic analysis. Results showed significant reductions in total dissolved solids from 396 to 182 mg.L-1 (54%), calcium carbonate from 424 to 228 mg.L-1 (46%), and alkalinity from 298 to 48 mg.L-1 (84%). Boiling the filtered water further improved water quality. The system maintained a steady discharge rate of 1.4 m³.h-1 and hydraulic retention times between 13.1 and 26.2 seconds, with minimal head loss. These findings confirm that the simple filtration system is both technically feasible and economically viable for household application, offering substantial benefits for water quality improvement and public health in rural limestone-affected communities. Keywords:  lime water, mulyosari hamlet, environmental health, simple water filtration, drinkable water